Higgs mass in noncommutative geometry1. Issue 9 (5th May 2014) - Devastato, A.; Lizzi, F.; Martinetti, P.
Abstract: In the noncommutative geometry approach to the standard model, an extra scalar field σ – initially suggested by particle physicist to stabilize the electroweak vacuum – makes the computation of the Higgs mass compatible with the 126 GeV experimental value. We give a brief account on how to generate this field from the Majorana mass of the neutrino, following the principles of noncommutative geometry.